National culture and operations management: a structured literature review. Issue 18 (17th September 2018) - Boscari, Stefania; Bortolotti, Thomas; Netland, Torbjørn H.; Rich, Nick
Abstract : National culture has received a substantial amount of interest in the operations management literature. We present the first structured review of articles studying national culture in operations management. Our search returned 51 papers published in ten leading journals between 2000 and 2017. We sort and analyse the papers according to three focus areas of operations management ( strategy, execution and improvement ). We also analyse the papers according to whether they address the relevance of national culture, the impact of national culture or the actions managers can use to manage or mitigate the effects of national culture. We find that national culture appears as a relevant variable in all focus areas of operations management research but that the direction and strength of its impact remain undetermined. Only a handful of papers address how managers can actively deal with challenges related to national culture. We propose a research agenda and a guiding framework for future research.